Alamat ng P-Pop exploring Magiliws' perceptions of alamat - Enerio, Victoria Regina M.; Marturillas, Jeza Marie B.; Miano, Gabrielaine Jane O. (College of Communication, Art, and Design , University of the Philippines Cebu, 2024)
This thesis study intends to contribute to the broader field of Philippine pop culture studies, focusing on multilingualism in music. ALAMAT, a P-Pop group formed by Ninuno Media, stands out in how they incorporate several Filipino languages in their songs: Ilocano, Bicolano, Waray-Waray, Bisaya, Kapampangan, Zambal, and Hiligaynon. Their multilingual lyrics have been branded as the counter-Kpop concept, setting them apart from other P-Pop groups. The group has since earned a diverse following, with its fans coming from different regions of the Philippines. The study examines ALAMAT's fandom, the Magiliws. Amidst actively supporting ALAMAT and engaging with fellow members of the community, Magiliws are bound to develop perceptions of the various regional languages and the people who speak them. Thus, this interaction makes Magiliws the ideal subject of the study. The discussion delves into ALAMAT's official releases, collaborations, and fan engagements, showcasing how ALAMAT fosters pride in regional languages and cultural heritage. Perspectives from Magiliws are thematically analyzed and discussed using Social Identity Theory, Cultural Proximity Theory, and Uses and Gratifications Theory. Five themes are found in this study, namely: 1) Pinoy/P-pop Pride; 2) Fan Community and Activity; 3) Representation of Sociolinguistic Identity; 4) Acknowledgement of Diversity in the Philippines; and 5) Self-Actualization and Growth. It is found that the Magiliw fandom takes pride in ALAMAT?s unique concept. They have a strong sense of belonging and advocacy, and this shows in their interest in the other regional languages featured, their desire for educational content, and further cultural representation. ALAMAT catalyzes Magiliws? self-actualization and reconnection with linguistic roots, reflecting ALAMAT?s impact beyond entertainment.